Structure characterization of molecular complexes for non-linear optical materials. II. 1 : 1 complexes of 4-methyl-morpholine-N-oxide (1) and 3-picoline-N-oxide (2) with 2,4,6-trinitrophenol, studied by X-ray, AM1 and DFT calculations - Zukerman-Schpector, Julio; Vega-Teijido, Mauricio; Carvalho, Cristina C.; Isolani, Paulo C.; Caracelli, Ignez (Oldenbourg Verlag, 2007)
(1) C6H2N3O7- center dot C5H12NO2+, Mr = 346.26, P2(1)/c, a = 7.2356(6), b = 10.5765(9), c = 19.593(2) angstrom, 3 beta=95.101(6)degrees, V = 1493.5(2) angstrom(3), Z = 4, R-1 = 0.0414; (2) C6H2N3O7- center dot C6H8NO+, Mr = 38.24, P2(1)/n, a = 7.8713(5), b = 6.1979(7), c = 28.697(3) angstrom, beta = 90.028(7)degrees, V = 1400.0(2) angstrom(3), Z = 4, R-1 = 0.0416. The packing units in both compounds consist of hydrogen bonded cation-anion pairs. The (hyper)polarizabilities have been calculated for the crystallographic and optimized molecules, by AM1 and at the DFT/B3LYP(6-31G**) level.
Keywords: supramolecular synthesis; hydrogen bond; picrate; (hyper)polarizability; semiempirical AM1; single crystal structure analysis; X-ray diffraction